GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN KINERJA GURU DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN SEKOLAH DI TK AL IQRA MATARAM DAN TK IT ANAK SHOLEH MATARAM - Handriani, Syifa’ Febrian; Makki, Muhammad; Hakim, Mansur; Mustari, Mohamad; Fahruddin, Fahruddin (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the transformational leadership style of school principals and teachers’ performance in improving school management effectiveness at TK Al Iqra Mataram and TK IT Anak Sholeh Mataram. This research employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, participatory observation, and document analysis. The result showed that principals leadership style has proven to contribute to improving the effectiveness of school management, particularly in terms of work coordination, programme planning, and the implementation of school activities. Furthermore, teachers’ performance in enhancing the effectiveness of school management indicates that the majority of teachers have performed their duties well, particularly in lesson planning, the delivery of teaching and learning activities, and participation in school activities. This teacher performance also supports the effectiveness of school management, particularly in creating a conducive working environment and achieving educational objectives.